Long-Term Continuous Extraction of Medium-Chain Carboxylates by Pertraction With Submerged Hollow-Fiber Membranes - Xu, Jiajie; Bian, Bin; Angenent, Largus T.; Saikaly, Pascal E. (Frontiers in Bioengineering and Biotechnology, 2021)
Medium-chain carboxylic acids (MCCAs), which can be generated from organic waste and agro-industrial side streams through microbial chain elongation, are valuable chemicals with numerous industrial applications. Membrane-based liquid-liquid extraction (pertraction) as a downstream separation process to extract MCCAs has been applied successfully. Here, a novel pertraction system with submerged hollow-fiber membranes in the fermentation bioreactor was applied to increase the MCCA extraction rate and reduce the footprint. The highest average surface-corrected MCCA extraction rate of 655.2 ± 86.4 mmol C m-2 d-1 was obtained, which was higher than any other previous reports, albeit the relatively small surface area removed only 11.6% of the introduced carbon via pertraction. This submerged extraction system was able to continuously extract MCCAs with a high extraction rate for more than 8 months. The average extraction rate of MCCA by internal membrane was 3.0- to 4.7-fold higher than the external pertraction (traditional pertraction) in the same bioreactor. A broth upflow velocity of 7.6 m h-1 was more efficient to extract MCCAs when compared to periodic biogas recirculation operation as a means to prevent membrane fouling. An even higher broth upflow velocity of 40.5 m h-1 resulted in a significant increase in methane production, losing more than 30% of carbon conversion to methane due to a loss of H2, and a subsequent drop in the H2 partial pressure. This resulted in the shift from a microbial community with chain elongators as the key functional group to methanogens, because the drop in H2 partial pressure led to thermodynamic conditions that oxidizes ethanol and carboxylic acids to acetate and H2 with methanogens as the syntrophic partner. Thus, operators of chain elongating systems should monitor the H2 partial pressure when changes in operating conditions are made.